Multi Agent System Based Risk Allocation Model for Public-Private-Partnership Type Projects (RAMP3) - Aladag, Hande; Isik, Zeynep (TURKISH CHAMBER CIVIL ENGINEERS, 2022)
The performance of the Public Private Partnership (PPP) projects depends on the efficiency of the risk allocation strategies between the public and private parties. Therefore, a multi agent system-based Risk Allocation Model for PPP projects (RAMP(3)) was developed to determine the proper risk allocation decisions between the public and private parties within the study. The methodology of RAMP(3) involves i) identification of risks by agents, ii) assessment of each risk's importance and impact, iii) communication of agents to negotiate on risk allocation decision and iv) determination of strategies and utility functions to be used in negotiation process. Focus of the study is presenting the steps of negotiation process of agents using economic theory and Zeuthen bargaining strategy. RAMP(3) was validated on two real PPP projects and results show that the higher risk value of an agent gets, agent's utility due to counter agent in that concession round lowers. Preliminary findings also show that risk is allocated to the party that has a higher risk acceptability in negotiation process. The RAMP(3) will enable project parties to determine the appropriate risk allocation strategies by considering the effects of emerging risks in terms of time delay, cost overrun and conflict and provide contract success. The model can also be used as a decision support system by public partner for performing an efficient and accurate risk allocation.
Keywords: Construction industry; construction projects; Multi-Agent System (MAS); Public Private Partnership (PPP); risk management; CONSTRUCTION; NEGOTIATION; Engineering